A new access route to dimetal sandwich complexes, including a radical anion. Issue 87 (17th October 2018) - Labrum, Nicholas S.; Losovyj, Yaroslav; Caulton, Kenneth G.
Abstract : A new approach for the synthesis of low valent metal sandwich complexes showing the unanticipated ease with which silylamides can function as leaving groups resulting in a 1D polymer of the repeating unit, [K(18-crown-6)][Cr2 (C10 H8 )2 ], has been described. Abstract : The amide in Cr[N(SiMe3 )2 ]2 (THF)2 is displaced by equimolar [K(18-crown-6)][naphthalene] to form the dimetal sandwich Cr2 (naphthalene)2 − as a radical anion paired with [K(18-crown-6)] + . Two Cr atoms in the sandwich do not form any multiple Cr/Cr bonds, and instead each interacts with one naphthalene in an η 6 fashion and with the second naphthalene in an η 4 connectivity mode. The naphthalene C/C distances show the effect of back donation from two chromium atoms to a greater extent than simply by 1 electron ring reduction, in comparison to the naphthalene radical anion. The SOMO of the product was established by variable temperature EPR spectroscopy, and the atom ratios and elemental purity were supported by XPS. The possible generality of the displacement of N(SiMe3 )2 − from a low valent metal is discussed.